Potential predation of commercial hemipterans on Drosophila suzukii (Diptera: Drosophilidae) eggs - Pérez-Guerrero, Sergio; Molina-Rodríguez, José María (Revista Colombiana de Entomología, 2017)
Drosophila suzukii is an exotic and invasive pest (from South East Asia) affecting a wide range of important crops from Europe and America, especially berries. This work analyzes potential predation of some commercial hemipterans on D. suzukii eggs under laboratory conditions using blueberry fruits. Three treatments were established: infested fruit + predator, no-infested fruit + predator (control) and no-infested fruit without predator (control). After 72 h, predators were removed, and the numbers of live and dead recorded. The mean number of D. suzukii adults that emerged per fruit was compared with number of adults that emerged from the control group. Numbers of live and dead predators from infested fruits treatment were compared with numbers of live and dead predators from the no-infested fruit control group. Among tested predators, only Anthocoris nemoralis displayed a significant reduction on adult’s emergence ( 50 %). No significant differences in the mean number of D. suzukii emerged adults per fruit were found for the treatments with Orius laevigatus, Macrolophus pygmaeus and Nesidiocoris tenuis, although N. tenuis showed significant higher survival rates when kept with infested fruits. Further and extended research is required in order to confirm the potential predation of A. nemoralis on D. suzukii eggs reported here.